An Evaluation of the Civil Service Merit System Protection Agency - Kulsudjarit, Amornrat; Singkaneti, Banjerd; Kaewla-iad, Supreeya; Nuchprayool, Bajrawan; Suntapun, Chanit; Sahapattana, Prapon (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The Merit System Protection in the Thai Civil Servant System was originally under the authority of a special subcommission (Special CSSC) appointed by the Civil service Commission. According to the Civil Service Act, B.E. 2551 (2008), it was restructured and the Merit System Protection Commission (MSPC) now has the powers and duties pertaining to considerations of appeals in case of a civil servant who was subject of a disciplinary punishment or who was discharged from government service and considerations of complaints as well as in case of a civil servant who has a cause for grievance caused by the treatment or non-treatment of oneself by the supervising official. The MSPC consists of commissioners appointed by the King. The MSPC commissioners hold office for a term of six years and only one term. The MSPC becomes an agency playing vital roles in the preservation, supervision and protection of the merit system with regard to human resource management of the civil service system according to the merit system. A civil servant who disagrees with the MSPC’s consideration is eligible to submit a legal complaint to the Administration Court according to the procedure specified by law. Thereby, it is appropriate to evaluate the current roles, structure and authority of the Civil Service Merit System Protection Agency to determine how efficient and effective its performance is and to develop a set of guidelines for the efficient Civil Service Merit System Protection Agency in the future.